2013
DOI: 10.1371/journal.pntd.0002459
|View full text |Cite
|
Sign up to set email alerts
|

Southernmost Asia Is the Source of Japanese Encephalitis Virus (Genotype 1) Diversity from which the Viruses Disperse and Evolve throughout Asia

Abstract: BackgroundAlthough a previous study predicted that Japanese encephalitis virus (JEV) originated in the Malaysia/Indonesia region, the virus is known to circulate mainly on the Asian continent. However, there are no reported systematic studies that adequately define how JEV then dispersed throughout Asia.Methodology/Principal FindingsIn order to understand the mode of JEV dispersal throughout the entire Asian continent and the factors that determine the dispersal characteristics of JEV, a phylogenetic analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(61 citation statements)
references
References 30 publications
6
55
0
Order By: Relevance
“…Until recently, most of the strains of JEV at the origin of major epidemics in the South, East, and Southeast Asia regions belonged to genotype III [18]. However, a shift in prevalence from JEV genotype III to JEV genotype I has been observed in several Asian countries [19][20][21], although an evolutionary study has demonstrated that three genotypes (I, III, V) were confirmed to be co-circulating in China in both high and low prevalence areas [22]. All JEV strains belong to a single serotype, as evident from an epidemiological observation of the absence of secondary encephalitis [23].…”
mentioning
confidence: 99%
“…Until recently, most of the strains of JEV at the origin of major epidemics in the South, East, and Southeast Asia regions belonged to genotype III [18]. However, a shift in prevalence from JEV genotype III to JEV genotype I has been observed in several Asian countries [19][20][21], although an evolutionary study has demonstrated that three genotypes (I, III, V) were confirmed to be co-circulating in China in both high and low prevalence areas [22]. All JEV strains belong to a single serotype, as evident from an epidemiological observation of the absence of secondary encephalitis [23].…”
mentioning
confidence: 99%
“…From the isolation of the prototype strain of JEV in 1935 until recently, most of the circulating strains of JEV belonged to g3 and were at the origin of major epidemics in Southeast Asian countries (5). Recently, a shift in prevalence from JEV g3 to g1 has been observed in several Asian countries (6)(7)(8), while some strains of JEV g5 have been occasionally isolated in China in 2009 (9) and in South Korea in 2010 (10). The JEV g5 prototype strain, strain Muar, was originally isolated in 1952 from an encephalitis patient in Malaysia (11) and was found to be genetically and serologically distinct from other genotypes (12)(13)(14).…”
mentioning
confidence: 99%
“…some indirect overseas evidence does exist: (i) JEV genotype 1 (G1) strain since 20 0 0: In Southeast Asia, studies reported that Genotype 3 was predominant during the late 20th century, and then genotype 1 started to replace genotype 3 around 20 0 0 and become dominant thereafter ( Gao et al, 2015;Mackenzie et al, 2004;Pan et al, 2011 ). One genetic study found that the genotype 1 strain was not observed until 2008 in the regions of Mainland China surrounding Hong Kong ( Gao et al, 2013 ). Thus, it is very likely that there is a newly introduced JEV strain from pigs imported from these Mainland Chinese regions ( The Government of Hong Kong, Agriculture, Fisheries and Conservation Department, 2017b ); (ii) JEV genotype 5 (G5) strain: Similar JEV resurgences were observed in South Korea in 1998 and 2010 ( Sunwoo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is very likely that there is a newly introduced JEV strain from pigs imported from these Mainland Chinese regions ( The Government of Hong Kong, Agriculture, Fisheries and Conservation Department, 2017b ); (ii) JEV genotype 5 (G5) strain: Similar JEV resurgences were observed in South Korea in 1998 and 2010 ( Sunwoo et al, 2016 ). The resurgence in 1998 was likely due to the introduction of G1 strain in the mid-1990's ( Gao et al, 2013;Mackenzie et al, 2004 ). The first isolated local G5 strain was reported in 2010 in South Korea, which coincided with the resurgence of JEV in 2010 ( Takhampunya et al, 2011 ), where the average number of annual JEV cases increased approximately six-to eight-fold ( Sunwoo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%